If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 6) = 3(x + -1) + -15 Reorder the terms: 2(6 + x) = 3(x + -1) + -15 (6 * 2 + x * 2) = 3(x + -1) + -15 (12 + 2x) = 3(x + -1) + -15 Reorder the terms: 12 + 2x = 3(-1 + x) + -15 12 + 2x = (-1 * 3 + x * 3) + -15 12 + 2x = (-3 + 3x) + -15 Reorder the terms: 12 + 2x = -3 + -15 + 3x Combine like terms: -3 + -15 = -18 12 + 2x = -18 + 3x Solving 12 + 2x = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 2x + -3x = -18 + 3x + -3x Combine like terms: 2x + -3x = -1x 12 + -1x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + -1x = -18 + 0 12 + -1x = -18 Add '-12' to each side of the equation. 12 + -12 + -1x = -18 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = -18 + -12 -1x = -18 + -12 Combine like terms: -18 + -12 = -30 -1x = -30 Divide each side by '-1'. x = 30 Simplifying x = 30
| r^4+30r^2=11r^3 | | 5.1x+4=4.1x | | 4x^4=100x^2 | | 1.6x+x=61 | | 4z^3=4z^2+24z | | y^3-3y^2+2y=0 | | 10x^2=20x+80 | | =7h+40 | | 2w+3(w+4)=27 | | 8*(0.5x-1)=12 | | 6*(x-2)=4*(x+4) | | 2x+2y-12=0 | | 3*(x-1)=2*(x-4) | | 16-7d=-3d-2 | | 5*(x+3)=35 | | 3x+2=10-x | | 2x+9=-29 | | 5d-4=-19 | | 6a+1=-5 | | 12+4p=4 | | 22=6b-8 | | (3x+5)-4x=3(2x-1)-4x | | 9y-8=8y-4 | | 2(x+3)+1=-7 | | 3(2x-5)-2=2(x-2) | | 7x+2(x+6)=39 | | -3(X+2)+1=X-25 | | 45-(3x+10)=3(x+7)+x | | 2m+-6m=22 | | 8=12a-4 | | 5y-3+y+21=8y+30-6y | | 8x-3x-10=20 |